Purulent peritonitis and mediastinitis caused by iatrogenic perforation of the jejunum during application of mediastinal drainage in a 74-year-old woman after CABG – a case report - Nowicki, Rafał; Bielicki, Grzegorz; Marczak, Jakub; Czopnik, Piotr; Łysenko, Lidia; Mielczarek, Beata; Durek, Grażyna; Kustrzycki, Wojciech (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2010)
A case of a 74-year-old female admitted to our department for the planned procedure of coronary artery bypass grafting (CABG) is described. The patient was suffering from insulin-dependent diabetes and obesity. Her medical history revealed extensive surgical treatment in the abdominal cavity, such as: appendectomy, cholecystectomy, choledochoduodenostomy, right-sided adrenalectomy and total gastrectomy with oesophagoduodenostomy. The coronary revascularization procedure was performed with no early complications. However, a few days later, symptoms indicating a high jejunal fistula appeared. It was presumed that the jejunum was perforated during the routine application of mediastinal drainage, and it resulted in limited purulent peritonitis, and, in consequence, suppurative mediastinitis with sternum instability. The patient underwent two additional surgical procedures (closure of the jejunal fistula and sternum re-fixation with application of mediastinal irrigation drainage). In the following period extensive infection of surgical sites and respiratory insufficiency appeared. Only by applying topical negative pressure and long-lasting antibiotic therapy was it finally possible to control the infection. When partial wound healing was achieved the patient was referred to a district hospital for further treatment of the wounds.